Factors associated with non-specific low back pain in field hockey: A cross-sectional study of Premier and Division One players - Dobbin, N.; Getty, C.; Digweed, B. (PLOS ONE, 2024)
Objective To determine the extent to which various factors are associated with greater or lesser odds of reporting non-specific low back pain (NS-LBP) in field hockey.